2016
DOI: 10.1016/j.jbiomech.2016.10.050
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valves produce unphysiological flows which may contribute to thromboembolic events: An in-vitro study

Abstract: PurposeTranscatheter aortic valve implantation (TAVI) has been associated with large incidence of ischemic events, whose sources are still unclear. In fact, sub-acute complications cannot be directly related to the severity of the calcification in the host tissues, nor with catheter manipulation during the implant. A potential cause could be local flow perturbations introduced by the implantation approach, resulting in thrombo-embolic consequences. In particular, contrary to the surgical approach, TAVI preserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 48 publications
3
41
0
Order By: Relevance
“…Lesions at the surface of leaflets during the TAVI procedure, abnormal transvalvular flow pattern due to deformed stent and impaired leaflet kinetics, as well as areas of flow stasis within the stent or between the stent and the native aortic valve leaflets or aortic root may promote leaflet thrombosis 55. In turn, valve thrombosis, even if treated successfully with warfarin, may subsequently cause inflammation and fibrocalcific remodelling of leaflets (figure 1).…”
Section: Durability Of Transcatheter Bioprosthesesmentioning
confidence: 99%
“…Lesions at the surface of leaflets during the TAVI procedure, abnormal transvalvular flow pattern due to deformed stent and impaired leaflet kinetics, as well as areas of flow stasis within the stent or between the stent and the native aortic valve leaflets or aortic root may promote leaflet thrombosis 55. In turn, valve thrombosis, even if treated successfully with warfarin, may subsequently cause inflammation and fibrocalcific remodelling of leaflets (figure 1).…”
Section: Durability Of Transcatheter Bioprosthesesmentioning
confidence: 99%
“…Although, a previous case report showed that patients who developed self‐expandable bioprosthetic valve thrombosis after TAVR had deep valve implantation depth (8 mm), our study is the first to show the association between valve implantation depth and worsening transprosthetic mean gradients after TAVR. On pathologic review, valve thrombosis occurs in the NCC or RCC more commonly and in vitro experiments suggest that the presence of TAV and the native AV in the paravalvular space produces non‐physiological flow in the aortic root that leads to stagnation at the aortic sinuses . After TAVR, native valve leaflets are expanded by the valve frame and formulate the cylindrical wall .…”
Section: Discussionmentioning
confidence: 99%
“…29 After TAVR, native valve leaflets are expanded by the valve frame and formulate the cylindrical wall. 29,30 When valves were implanted in a deeper position within the LVOT, it is possible that a neo-sinus created between the native valve and the artificial AV can be a nidus for thrombosis ( Figure 6). This may also increase the exposed area of the native valve and exaggerate the non-physiological flow in aortic root.…”
Section: Variables Related To Valve Stenosismentioning
confidence: 99%
“…During the TAVI procedure, the native valve leaflets are compressed between the prosthetic valve and aortic wall. This environment is associated with an extended zone of flow stagnation zone at the base of the sinus that may promote thrombus formation resulting in valve leaflet thrombosis and/or embolic events 19. Whether thrombus formation might lead to further progressive leaflet structural changes and eventually SVD is yet unknown.…”
Section: How Does Valve Thrombosis Relate To Svd?mentioning
confidence: 99%